A Survey on Partial Reconfiguration Techniques (International Journal of Engineering and Computer Science, 2017)
The technology evolvement has led to incorporation of more and more features into the system. One such feature is the flexibility of changing the hardware and software at the time of fabrication. Such a feature is called reconfiguration. The reconfiguration allows the user to incorporate more control over the hardware and software even at final stages of the process. Such type of reconfiguration is possible in Field Programmable Gate Array (FPGA).  There are various classifications of reconfiguration based on application of reconfiguring a device usually FPGA. In this paper we go through the overview of partial reconfiguration and various techniques employed to achieve it.